Kode Etik Pustakawan sebagai Aturan Profesional bagi Profesi Pustakawan - Kumala, Anggi; Permana, Bagus Gigih; Yendri, Bunga Arbiyati; Purba, Risky Akbar (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2023)
The librarian code of ethics as a professional rule for the librarian profession. The librarian code of ethics is a set of rules governing the ethical behavior expected of a librarian. The purpose of the code is to promote integrity, professionalism, and social responsibility in the practice of librarianship. The methodology used was a literature review of various sources of books, journal articles, and professional websites relevant to the librarian code of ethics. The results of the literature review show that a code of ethics generally consists of a set of ethical principles, values, and standards that form professional guidelines. They enable librarians to confront and solve ethical issues that arise in their practice. In this journal, we will discuss the librarian's code of ethics and how it shapes professional practice in the librarian profession.